The Role Of Media In Promoting Corporate Social Responsibility On Environment Sustainability - Dorien Kartikawangi, Dorien Kartikawangi (2015)
Corporate Social Responsibility (hereinafter will be referred to as CSR) which has been recognized in Indonesia since 1945 (Serad, 2012) is one of important pillars in empowering community by placing corporates as government’s important partners. Despite the improving implementation, by not only exercising its obligation stipulated by the government, there are still spaces to optimize strategic role of this type of program. Evaluation and sustainability of programs are rarely conducted therefore the effect on community in the long run sometimes does not obtain any attention.